Self‐Assembled Plasmonic Coaxial Nanocavities for High‐Definition Broad‐Angle Coloring in Reflection and Transmission. Issue 10 (18th March 2021) - Ni, Haibin; Krasavin, Alexey V.; Zhang, Lu; Ping, An; Pan, Chao; Cheng, Jianxin; Wang, Ming; Chang, Jianhua; Zayats, Anatoly V.
Abstract: Resonant spectral scattering from metallic nanostructures is an attractive alternative approach to produce colors instead of using chemical pigments. Here, a technological platform based on self‐assembled arrays of coaxial plasmonic resonators is developed for generating a bright color gamut over the entire visible spectral range in both reflection and transmission, offering the potential for ultrahigh definition coloring over large areas. Unlike the approaches using the nanostructure periodicity to define colors, the developed method employs color engineering based on the localized plasmon resonances in nanocavities, therefore, providing a broad angular response and viewing angles of up to 40°. With the nanoscale dimensions of color pixels and an increased viewing angle range, the proposed approach allows achieving large‐area color patterns with local coloring controlled by postprocessing, important for display technology, anticounterfeiting and artistic applications. Abstract : An inexpensive and scalable self‐assembly technique providing precise color engineering over an entire visible range and offering versatile application opportunities both in reflection and transmission is introduced. The implemented color definition is based on the excitation of localized surface plasmon modes in individual plasmonic nanostructures, which offers the possibility of the ultimately small pixel size approaching the diffraction limit.